Estimating the potential of biohydrogen production and carbon neutralization contribution from crop straw. (April 2023) - Liu, Tao; Li, Yameng; Zhang, Huan; Zhang, Ningyuan; Tahir, Nadeem; Zhang, Quanguo
Graphical abstract: Highlights: GM(1.1) was used to predict the crop straw yield of China. Using the cellulose degradation model to determine the specific biohydrogen yield. GHGs emission reduction potential of crop straw was assessed. Hydrogen yield of 1.31 × 10 11 m 3 could be produced from crop straw in China. Reduction of 2.42 × 10 8 t/a CO2 -eq from crop straw based biohydrogen in China. Abstract: In order to achieve the carbon neutrality goal set by Chinese government, the potential contribution of hydrogen production from crop residues by microbial fermentation technology and Greenhouse gas (GHGs) reduction have been studied. Firstly, the annual yield of crop straw was estimated according to crop yield and grass grain ratio, and then the grey model GM (1, 1) was applied to predict the crop residues resources available for hydrogen production in various provinces in China in 2021. The results showed that the maximum resource of straw being available for hydrogen production is about 4.54 × 10 8 t, corresponding to 1.31 × 10 11 m 3 of hydrogen, the energy carried by the obtained hydrogen was 73 % and 1.15 times than the energy of national civil natural gas consumption and energy of transportation gasoline consumption, respectively. The potential reduction of greenhouse gas emission was 2.42 × 10 8 t/a CO2 -eq, representing 2.4 % of GHGs emissions.